Physical activity parameters and Body Mass Index among Public Secondary School Teachers, Oyo State. Nigeria - Fabunmi, Ayodeji; Oyedokun, Barakat; Omole, John (Health Promotion & Physical Activity, 2019)
Introduction: Physical inactivity is an important contributor to obesity epidemic. In Nigeria, public secondary school teachers are prone to sedentary lifestyle. This study determined physical activity parameters and Body mass index (BMI) among public secondary school teachers in Ibadan North Local Government Area of Oyo State. It also compared physical activity parameters and BMI between male and female teachers. Materials and methods: This study is a cross sectional survey and 101 (65 females and 36 males) public secondary school teachers participated. Physical activity parameters (number of steps, distance covered and energy expenditure) were assessed using pedometer while the Body Mass Index (BMI) was computed from participant’s height and weight. Data were analyzed using descriptive (percentage, mean, standard deviation) and inferential (Independent ‘t’ test and Pearson product moment correlation coefficient) statistics. Alpha level was set at p<0. 05. Results: Participants mean age, BMI, number of steps and energy expenditure were 43.67±9.49 years, 26.70±5.55 kg/m2, 7429.06±5469.6 steps per day and 185.26± 158.64 kcal/day respectively. There was a negative, non-significant correlation between number of steps and BMI (r = -0.004, p = 0.969), a significant positive correlation between Energy Expenditure and number of steps taken (r = 0.766, p = 0.001) and a positive, non-significant correlation between Energy Expenditure and BMI (r = 0.150, p = 0.135). Females had significantly higher body weight and BMI than male teachers. Conclusions: Body weight and BMI was significantly higher among female than male participants. Men were physically active more than women but not significantly.